Pluralitas Umat Beragama: Upaya Menegakkan Toleransi melalui Al-Qur'an - Mawardi Mawardi; Idrus Ruslan (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
Conflicts between religions, intolerance and violence in the name of religion is on the rise in the recent years. Attitudes such as mutual suspicion, disrespect for each other, and disharmony of life have become a reality of life among religious communities. Without tolerance, harmony between religions will be difficult to realize, because tolerance is inevitable for religious communities. Tolerance is also part of the theology vision or Islamic Aqeeda as taught in the Quran. Therefore, in depth study on tolerance may help the stakeholders in their effort to minimize religious conflict and establish harmony among the religious believers.Abstrak: Dalam beberapa tahun terakhir ini sangat banyak muncul konflik antar agama, intoleransi dan kekerasan atas nama agama. Adanya sikap seperti saling mencurigai, tidak menghargai satu sama lain, dan ketidakharmonisan hidup telah menjadi sebuah realitas kehidupan antar umat beragama. Tanpa adanya toleransi, kerukunan hidup antar umat beragama akan sulit terwujud, karena toleransi merupakan suatu keniscayaan bagi umat beragama. Toleransi juga merupakan bagian dari visi teologi atau akidah Islam sebagaimana yang ajarkan di dalam Alqur’an. Olehkarenanya, kajian terhadap toleransi perlu dikaji secara mendalam sebagai upaya untuk meminimalisir konflik keagamaan dan terciptanya kerukunan hidup antarumat beragama.